2010
DOI: 10.1680/wama.2010.163.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Assessing activated sludge morphology by laser and image analysis

Abstract: An excess of filamentous bacteria is a common settlement problem affecting the activated sludge process. In this study activated sludge morphology was monitored by image analysis and laser scattering. These were compared with the conventional sludge volume index. Good correlations between the two optical techniques for floc size were found when the small and interfering particles (< 50 ìm) were removed from the analysis (activated sludge size 100-500 ìm). A simpler image analysis procedure was developed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…indicated that the apparent K O,AOB was higher than K O,NOB when the floc size was above 100 µm diameter. Since the activated sludge floc diameter was usually above 100 µm, this explained the high apparent NOB oxygen half‐saturation index reported in the literature …”
Section: Discussionmentioning
confidence: 98%
“…indicated that the apparent K O,AOB was higher than K O,NOB when the floc size was above 100 µm diameter. Since the activated sludge floc diameter was usually above 100 µm, this explained the high apparent NOB oxygen half‐saturation index reported in the literature …”
Section: Discussionmentioning
confidence: 98%
“…An excess of filamentous bacteria is a common settlement problem affecting the activated sludge process. In the paper by Wu and Wheatley (2010), the activated sludge morphology was monitored by image analysis and laser scattering. These were compared with the conventional sludge volume index (SVI).…”
mentioning
confidence: 99%
“…The second, third and fourth papers describe solutions to improve river water quality through the design of detention ponds, (Prohaska et al, 2010); design of biological aerated filters for the treatment of food-related industrial effluents (Osorio et al, 2010); and improvements to monitoring of the activated sludge process used to treat sewage (Wu and Wheatley, 2010). The fifth paper (Rao et al, 2010) continues with the water quality theme but focuses on the issue of drinking water quality, evaluating the use of magnesium oxide in India to reduce excessive fluoride levels.…”
mentioning
confidence: 99%